Persistent and progressive long-term lung disease in survivors of preterm birth - Urs, Rhea; Kotecha, S.; Hall, Graham; Simpson, S. (W.B. Saunders Co. Ltd., 2018)
© 2018 Elsevier Ltd. Preterm birth accounts for approximately 11% of births globally, with rates increasing across many countries. Concurrent advances in neonatal care have led to increased survival of infants of lower gestational age (GA). However, infants born < 32 weeks of GA experience adverse respiratory outcomes, manifesting with increased respiratory symptoms, hospitalisation and health care utilisation into early childhood. The development of bronchopulmonary dysplasia (BPD) – the chronic lung disease of prematurity – further increases the risk of poor respiratory outcomes throughout childhood, into adolescence and adulthood. Indeed, survivors of preterm birth have shown increased respiratory symptoms, altered lung structure, persistent and even declining lung function throughout childhood. The mechanisms behind this persistent and sometimes progressive lung disease are unclear, and the implications place those born preterm at increased risk of respiratory morbidity into adulthood. This review aims to summarise what is known about the long-term pulmonary outcomes of contemporary preterm birth, examine the possible mechanisms of long-term respiratory morbidity in those born preterm and discuss addressing the unknowns and potentials for targeted treatments.